Parameter Optimization Analysis of Prolonged Analgesia Effect of tDCS on Neuropathic Pain Rats - Wen, Hui-Zhong; Gao, Shi-Hao; Zhao, Yan-Dong; He, Wen-Juan; Tian, Xue-Long; Ruan, Huai-Zhen (Frontiers in Behavioral Neuroscience, 2017)
Background: Transcranial Direct Current Stimulation (tDCS) is widely used to treat human nerve disorders and neuropathic pain by modulating the excitability of cortex. The effectiveness of tDCS is influenced by its stimulation parameters, but there have been no systematic studies to help guide the selection of different parameters. Objective: This study aims to assess the effects of tDCS of primary motor cortex (M1) on chronic neuropathic pain in rats and to test for the optimal parameter combinations for analgesia. Methods: Using the chronic neuropathic pain models of chronic constriction injury (CCI), we measured pain thresholds before and after anodal-tDCS (A-tDCS) using different parameter conditions, including stimulation intensity, stimulation time, intervention time, and electrode located (ipsilateral or contralateral M1 of the ligated paw on male/female CCI models). Results: Following the application of A-tDCS over M1, we observed that the antinociceptive effects were depended on different parameters. Firstly, we found that repetitive A-tDCS had a longer analgesic effect than single stimulus, and both ipsilateral-tDCS (ip-tDCS) and contralateral-tDCS (con-tDCS) produce a long-lasting analgesic effect on neuropathic pain. Secondly, the antinociceptive effects were intensity-dependent and time- dependent, high intensities worked better than low intensities and long stimulus durations worked better than short stimulus durations. Thirdly, timing of the intervention after injury affected the stimulation outcome, early use of tDCS was an effective method to prevent the development of pain, and more frequent intervention induced more analgesia in CCI rats, finally, similar antinociceptive effects of con- and ip- tDCS were observed in both sexes of CCI rats. Conclusions: Optimized protocols of tDCS for treating antinociceptive effects were developed. These findings should be taken into consideration when using tDCS to produce analgesic effects in clinical applications.